PENERAPAN METODE PROFILE MATCHING DAN FUZZY SAW DALAM MENENTUKAN SEKOLAH MADRASAH IBTIDAIYAH TERBAIK - Rida Utami; Nahar Maganda Saragih; Yahya Tanjung (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Currently the Office of the Ministry of Religion Kab. Langkat has not yet used the system to make decisions related to the Selection of the Best Madrasah Ibtidaiyah. Previously, the community only asked neighbors to find out whether the madrasa was the best or not. The problem that occurs in the community is that there is no effective data to prove whether the madrasa is the best or not. For this reason, we need a system that can assist the Ministry of Religion in making decisions regarding the selection of the best primary school by providing alternative choices by considering several elements of each of the predetermined criteria. As for the results of the study: The decision support system application that was built can provide decisions in selecting the best primary school.